Chinese Commercial Banks Risk Management Practices: A Research in China Banking Risk Management - Wang, Xiaoling (2006)
This dissertation uses a qualitative research approach, and examines the importance and its current situation of banks risk management in China banking. The commercial banking analysis covers China state-own commercial banks and joint-stock commercial banks as well as local city commercial banks, but mainly analysis stems from state-owned and joint-stock commercial banks, excluding foreign banks in China. In addition, this dissertation reveals that China Center Bank and China Bank Regulatory Commission have fulfilled management strategies under Basel II new frameworks. The dissertation was conducted during the summer of 2006. The information obtained covers both the literature and practice of financial risk management. This dissertation concludes the results of this research. It reports the risk management techniques in the banking, and reports the practice of risk management in China banking, and discuses the fierce challenges that China banking is facing and how evaluate their risk management level in China banking. Keywords: Risk Management, Research Approach, China Banking